Effect of Underwriter’s Reputation on Performance of small business IPOs - P. Siwach; P. R. Kumar; V. Gupta (Финансы: теория и практика, 2023)
The purpose of the study is to determine the impact of the underwriter’s reputation on shaping the short- and long-term IPO success of small businesses. The paper uses IPO data from 2012 to 2020, three reputable proxy and event-time methodologies to analyze the company’s performance through market-adjusted excess returns, cumulative abnormal returns and buy & hold returns. Similarly, to mitigate common predispositions, use the calendar-time methodology, Fama-French three-factor model and Carhart four-factor model with high and low reputational groups. The study revealed a significant positive impact of underwriters’ reputations on first-day returns and long-term performance. Overall, the results indicate that, in the longterm, IPOs of Indian small and medium-sized enterprises are over efficient with regard to reputation signals. On the contrary, the calendar-time method and multifactor model indicate the low long-term IPO effectiveness of the SME. According to the authors’ conclusion, this is the first study to assess the impact of underwriter reputation on business performance using several reputation indicators, the calendar time methodology, and the multi-factor model on the ICP’s Indian IPO platform.